1990
DOI: 10.1002/ptr.2650040403
|View full text |Cite
|
Sign up to set email alerts
|

Olea europaea L. and oleuropein: Effects on excito‐conduction and on monophasic action potential in anaesthetized dogs

Abstract: The effects of a glyceroethanolic macerate of the leaves of Olea europaea L. and of oleuropein on excito-conduction and on the right atrial and ventricular monophasic action potential (MAP) have been studied in anaesthetized dogs using the technique of endocavitary recording. At the higher doses tested, a slight increase in the sinusal cycle of the sinoatrial conduction time and of the sinus node recovery time, together with a prolongation of the atrioventricular and intraventricular conduction and an increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
7
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
2
7
0
Order By: Relevance
“…Nevertheless, a possible differentiation between oleuropein and its alcoholic component concerning the mode of action is reported in this paper for the first time. These results may coincide with Occhiuto et al (1990) and Zarzuelo et al (1991) who reported in their recent pharmacological investigations on Olea europaea that, in addition to oleuropein, at least one other active compound must be present in this drug. The pharmacologically most active extract of Peucedanum rhizomes was obtained by using n-hexane as solvent (Fig.…”
Section: O G L Csupporting
confidence: 89%
See 1 more Smart Citation
“…Nevertheless, a possible differentiation between oleuropein and its alcoholic component concerning the mode of action is reported in this paper for the first time. These results may coincide with Occhiuto et al (1990) and Zarzuelo et al (1991) who reported in their recent pharmacological investigations on Olea europaea that, in addition to oleuropein, at least one other active compound must be present in this drug. The pharmacologically most active extract of Peucedanum rhizomes was obtained by using n-hexane as solvent (Fig.…”
Section: O G L Csupporting
confidence: 89%
“…Diluted alcoholic extracts are spasmolytic, antiarhythmic and hypotensive (Petkov, 1979) and influence monophasic action potential in anaesthetized dogs (Occhiuto et a/., 1990) In some feucedanum species furanocoumarins with calcium-channel blocking activity have been found (Vuorela et al, 1986); apart from such compounds, f . ostruthium contains coumarins that have not been investigated yet German name 'Herzgespannkraut', spasmolytic, antihypertensive and negative inotropic properties have been reported (Reuter and Diehl, 1970) but have not been confirmed on a phytochemical basis (Wichtl, 1990) yet operated-channels (ROC).…”
Section: Introductionmentioning
confidence: 99%
“…Leaf extracts of Olea europaea L. (Oleaceae) produce cardiovascular effects characterized by a decrease in cardiac contractility, atrial rate and arterial blood pressure in either normotensive (1,2) or DOCA-salt hypertensive rats (1), vascular smooth muscle relaxation (2) and antiarrhythmic effects (3). Oleuropeoside [2-(3 ,4-dihydro-xyphenyl)-ethyl (2S,4S)-3-E-ethylldene-2-(J3-n-glucopyranosyloxy)-5-methoxycarbonyl-3 ,4-dihydro-2H-pyran-4-ylacetate], a secoiridoid isolated from olive leaves (2,4,5), has been considered as one of its active principles (2,6). Recently, Occhiuto et al (6) found that high doses of a glyceroethanolic macerate from ohve leaves and oleuropeoside slowed atrioventricular and intraventricular but not intraatrial conduction and increased the duration of the monophasic atrial and ventricular potentials recorded in anaesthesized dogs using endocavitary sucking electrodes.…”
Section: Introductionmentioning
confidence: 99%
“…Oleuropeoside [2-(3 ,4-dihydro-xyphenyl)-ethyl (2S,4S)-3-E-ethylldene-2-(J3-n-glucopyranosyloxy)-5-methoxycarbonyl-3 ,4-dihydro-2H-pyran-4-ylacetate], a secoiridoid isolated from olive leaves (2,4,5), has been considered as one of its active principles (2,6). Recently, Occhiuto et al (6) found that high doses of a glyceroethanolic macerate from ohve leaves and oleuropeoside slowed atrioventricular and intraventricular but not intraatrial conduction and increased the duration of the monophasic atrial and ventricular potentials recorded in anaesthesized dogs using endocavitary sucking electrodes. These results confirmed the negative chronotropic and dromotropic effects of the extract previously described in isolated rat and rabbit hearts (1,6).…”
Section: Introductionmentioning
confidence: 99%
“…The aqueous extracts of olive leaves inhibited angiotensin-converting enzyme (Hansen et al, 1996). Its leaves are also reported as antiarrhythmic (Occhiuto et al, 1990), antihypertensive (Lasserre et al, 1983) and vasodilatory (Zarzuelo et al, 1991). Oleuropein, an active principle of olive enhances nitric oxide production by mouse macrophages (Visioli et al, 1998).…”
mentioning
confidence: 99%